2018
DOI: 10.3329/bjch.v42i1.37045
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Measles among Children Admitted in Tertiary Care Hospital

Abstract: Background: Despite widespread vaccination against measles in Bangladesh outbreak continue to occur. The Objective of the study was to see the demographic characteristics of patients who had the diagnosis of measles at Dhaka Shishu (Children) Hospital and occurrence of measles from the time of vaccination.Methodology: This retrospective study was conducted on patient who were diagnosed as measles at Dhaka Shishu (Children) Hospital between 1st January 2017 to 30th April 2017. The diagnosis of measles based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…[12] Similar results were also presented by other authors. [13] In our study 35 (23.3%) had mild,45 (30%) cases had moderate and severity of measles was among 70 (46.7%) patients. [14] Prevalence of pneumonia was found among 95 (63.3%) cases.…”
Section: Discussionsupporting
confidence: 46%
“…[12] Similar results were also presented by other authors. [13] In our study 35 (23.3%) had mild,45 (30%) cases had moderate and severity of measles was among 70 (46.7%) patients. [14] Prevalence of pneumonia was found among 95 (63.3%) cases.…”
Section: Discussionsupporting
confidence: 46%
“…Here most patients belong to the age group of 9 months to 4 years. Ahsan et al showed maximum measles patients in the age group of 13-14 months (47.8%) followed by 9-12 months (34.8%) 11 . But Akramuzzaman et al in Bangladesh found 23% of measles cases found before 9 months of age and 19% between 9-11 months of hospitalized children admitted with Measles 12 .…”
Section: Resultsmentioning
confidence: 96%
“…Ahsan et al found 35% of measles cases from 9 month to 1 year and 48% in between 13-14 months. 14 In khan et al's study 78% of children was below 3 years. 7 In our study pneumonia was the main complication, 62(72%) followed by diarrhea 28(32%).…”
Section: Discussionmentioning
confidence: 94%
“…The overall complete (2 doses) vaccination status from 9 months to 10 year was 26% in our study which was 8.7% in Ahsan et al's atudy. 14 Measles patient of 9 months to 12 months were 27. Among them 41% received first dose of measles vaccine and 59% did not.…”
Section: Discussionmentioning
confidence: 99%